STRATEGI MANAJEMEN SUMBER DAYA MANUSIA ADAPTIF BERBASIS KEARIFAN LOKAL UNTUK PENGUATAN KEBERLANJUTAN ORGANISASI KEPEMUDAAN DI PADUKUHAN KEMIRI - Makmun, Muhammad Adib; Amin, Muhammad; Aisya, Azzah Rihadatul (khidmatan, 2025)
Youth organizations are strategic assets that often face critical challenges such as weak volunteer human resource management and organizational dormancy, as observed in Kemiri Hamlet. This community service project aims to implement an Adaptive Human Resource Management (HRM) Strategy using the Participatory Action Research (PAR) approach. This strategy was executed by repositioning the roles of youth and establishing flexible work mechanisms. The results demonstrate a systemic transformation through the renewal of a more functional organizational structure and the establishment of "Karawitan" (traditional music) as a cultural instrument to enhance member retention and engagement. The integration of local wisdom-based activities into the work program proved effective in increasing volunteer motivation and ensuring the institutional sustainability of the youth organization. This adaptive HRM approach successfully shifted the organizational pattern from a rigid structure to one based on interests and talents, which is crucial for the sustainability of volunteer organizations at the rural level.